The Role of Intensive Islamic Courses in Strengthening Religious Foundation Among Orphaned Children: a Case Study Of Yaa Bunayya Orphanage Under Mutiara Cahaya Qolbu Foundation in Teluk Dalam - Lubis, Hasan Hamzah; Tumanggor, Ilham; Siregar, Taufiq Hidayat; Imam Azhar (ASSUNNAH PRESS, 2025)
This study examines the critical role of intensive Islamic educational programs in establishing religious foundations among orphaned children in minority Muslim communities. Using an Asset-Based Community Development (ABCD) methodological framework, we conducted a detailed investigation at Yaa Bunayya Orphanage, operated by the Mutiara Cahaya Qolbu Foundation in Teluk Dalam, South Nias, Indonesia—a region where Muslims constitute only 2.4% of the population. Through systematic observation, structured interviews with community stakeholders, and documentation analysis during Ramadan-based community service initiatives, we identified significant educational challenges including limited qualified instructors, insufficient learning resources, and geographical isolation from established Islamic educational institutions. The implementation of an accelerated Islamic boarding school program (